2002
DOI: 10.1603/0022-0493-95.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Responses of <I>Coptotermes formosanus</I> and <I>Reticulitermes flavipes</I> (Isoptera: Rhinotermitidae) to Three Types of Wood Rot Fungi Cultured on Different Substrates

Abstract: This study examined the responses of two termite species, the Formosan subterranean termite, Coptotermes formosanus Shiraki, and the eastern subterranean termite, Reticulitermes flavipes (Kollar), to three types of wood decay fungi: a brown rot fungus, Gloeophyllum trabeum (Persoon: Fries) Murrill; a white rot fungus, Phanerochaete chrysosporium Burdsall; and a litter rot fungus, Marasmiellus troyanus (Murrill) Singer. We also examined the responses of termites to these three types of fungi grown on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Such dead wood properties have been classified into different decay types, such as white, brown, and soft rots according to the lignocellulosedecomposition capabilities of various fungal species. In addition, because the decomposition of lignocellulose is a key determinant of humus formation on the forest floor (Stevenson, 1982), decay types have marked effects on the species composition of detritus-dwelling organisms, such as bacteria (Jurgensen et al 1989;Folman et al 2008;Hoppe et al 2014), fungi (Tedersoo et al 2008;Lindner et al 2011), invertebrates (Araya, 1993;Cornelius et al 2002;Wardlaw et al 2009), and plants that grow above the detritus communities (Ba ce et al 2012;Fukasawa, 2012). Such effects could be recognized as indirect effects of fungi on detritus communities and plants, mediated by environmental changes in CWD.…”
Section: Introductionmentioning
confidence: 99%
“…Such dead wood properties have been classified into different decay types, such as white, brown, and soft rots according to the lignocellulosedecomposition capabilities of various fungal species. In addition, because the decomposition of lignocellulose is a key determinant of humus formation on the forest floor (Stevenson, 1982), decay types have marked effects on the species composition of detritus-dwelling organisms, such as bacteria (Jurgensen et al 1989;Folman et al 2008;Hoppe et al 2014), fungi (Tedersoo et al 2008;Lindner et al 2011), invertebrates (Araya, 1993;Cornelius et al 2002;Wardlaw et al 2009), and plants that grow above the detritus communities (Ba ce et al 2012;Fukasawa, 2012). Such effects could be recognized as indirect effects of fungi on detritus communities and plants, mediated by environmental changes in CWD.…”
Section: Introductionmentioning
confidence: 99%
“…Wood decomposition by fungi is classified into different decay types such as white-rot, brown-rot, and soft-rot, which indicate lignocellulose decomposition capabilities of the different fungal species (Eaton and Hale, 1993). Because decomposition of lignocellulose is a key factor controlling soil humus formation on the forest floor (Stevenson, 1982), decay type has significant effects on species composition of organisms in soil detritus-based food webs such as bacteria (Folman et al, 2008;Jergensen et al, 1989), ectomycorrhizal fungi (Tedersoo et al, 2008), termites (Cornelius et al, 2002), and beetle larvae (Araya, 1993;Wardlaw et al, 2009) that inhabit dead wood. Wood chemical properties including pH and organic content may control communities of organisms in woody debris (Jergensen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Smythe et al (1967) have reported that termites are attracted to decayed wood by wood decaying fungi, and many termite species also ingest excessive amounts of decayed wood than wood that is not decayed. Fungi associated with cellulolytic decay play an important role in termite nutrition and orientation to food materials (Cornelious et al, 2002), as the fungi can modify the texture of the wood to favour termite feeding and detoxify the toxic compounds present in plants (Beard, 1974;Jayasimha, 2006). Zoberi and Grace (1990) have reported the isolation of forty species of cellulolytic and pathogenic fungi associated with Reticulitermes flavifes (Koller).…”
Section: Introductionmentioning
confidence: 99%
“…A hypothesis formulated in the current investigation was that the biodiversity observed within and among the fungi assemblages could be correlated with the attraction of G. dilatatus to decayed stem. Hence the present study was initiated as a survey of fungi associated with termite infested decayed stems of the tea cultivar TRI 4042, living termites and termite galleries, as fungi play a positive role in wood decay and orientation of termites (Cornelious et al, 2002). The study was further extended to utilisation of carbon sources by selected fungal species, to investigate the ability of substrate utilisation and evaluate the ability to decompose structural and storage components in vitro using pure substrates.…”
Section: Introductionmentioning
confidence: 99%